Penyuluhan Integratif Ketahanan Pangan dan Gizi Keluarga di Bogor - Sari Dewi Kusuma; Fauzi Ramadhan; Rina Muthia Sari; Dian Pratama Putra; Laila Nurhayati; Hendra Gunawan; Wulan Puspitasari (Bakti Masyarakat Pengabdian dan Pemberdayaan Masyarakat, 2026)
Family food security and nutrition remain strategic issues requiring serious attention in Bogor City, where the prevalence of stunting still reaches 18.4% and nutritional imbalance is commonly found among vulnerable groups. This community service program aimed to improve knowledge, attitudes, and practices related to family food security and balanced nutrition through an integrative community-based education approach. The program was implemented for six months in ten urban villages in Bogor City using a participatory approach. Activities included weekly group counseling sessions, biweekly nutritious cooking demonstrations, development of family nutrition gardens, and home assistance by trained community cadres. The program involved 300 housewives, 120 posyandu cadres, and 80 health workers. The results showed a 74% increase in nutrition knowledge and a 68% improvement in dietary diversity scores. In addition, the prevalence of stunting among targeted toddlers decreased from 24.6% to 12.3%. Post-program evaluation indicated that 82% of participants applied balanced diets and 76% consistently utilized local food resources in Bogor.